Characterization of full-length HIV-1 CRF17_BF genomes and comparison to the prototype CRF12_BF strains - Aulicino, Paula (2012)
The aim of this work is to characterize the full-length intersubtype recombinant structure of the HIV-1 Circulating Recombinant Form CRF17_BF. A single genome of CRF17_BF was originally described in 2001 as being largely similar to CRF12_BF. Since then, more genomes of CRF17_BF have been sequenced but not adequately described in publications. Here we describe CRF17_BF as a genuine CRF, and analyze its recombination pattern based on bootscan analyses, subtype signature patterns, and phylogenetic reconstruction of subtype-delimited segments. We show that CRF17_BF can be distinguished from CRF12_BF in several regions of the genome, including vpu, pol, env and nef. A complete and accurate characterization and description of recombination breakpoints in CRFs is required for a proper surveillance of HIV-1 genotypes, and important for epidemiological purposes.